Climate change and the sustainable use of water resources - Leal Filho, Walter (Climate Change Management, 2012)
The book explores the geo-chemical, physical, social and economic impacts of climate change on water supplies. It contains examples and case studies from a wide range of countries, and addresses the need to promote sustainable water use across the world.